Representasi Sistem Mata Pencaharian Masyarakat Indramayu dalam Novel Aib Dan Nasib Karya Minanto - Suci Ayu Latifah (Balai Bahasa Provinsi Riau, 2022)
The aim of this study is to reveal the livelihood systems in Minanto's Aib dan Nasib novel. The novel tells about tumultuous village life of the rural people in Indramayu. One of them is related to typical economic system of rural lif,i.e. poverty problem. Poverty seems to be the curse of life. The study used descriptive qualitative method of which its object is Minanto’s Aib dan Nasib. Literature study and analytical descriptive techniques were used for data analysis. The findings show the diversity of livelihood systems in the community. They are sellers, pedicab drivers, weed seekers scavengers , teachers, public transportation drivers, preachers, , farmers, farm laborers, shop keepers, migrant workers, commercial sex workers, grave diggers, hospital workers, village health officer leaders of neighborhood organization, distributors of migrant workers, barbers, and office workers. These jobs are sources of livelihood . The livelihood system can be used as a life motivation that As the world keeps turning, life must go on . Although money is not the orientation of life, but we cannot deny its existence for human life.